The impact of financial discharge from methadone maintenance therapy on incarceration - Zaller, PhD, Nickolas D.; Fu, BSc, Jeannia J.; Bazazi, BA, Alexander R.; Rich, MD, MPH, Josiah D. (Journal of Opioid Management, 2018)
Objectives: The authors sought to analyze the relationship between financial discharge from methadone maintenance therapy (MMT) and subsequent involvement in the criminal justice system among individuals receiving state-subsidized MMT slots and individuals who were financially discharged from MMT. Methods: The authors examined state-level client treatment records from all individuals who were on a subsidized MMT slot and all individuals who were discharged due to their inability to pay (financial discharge) from one of the three MMT programs during an 18-month period. The authors cross-referenced these records, through a state-managed database, with records of the Department of Corrections. Results: Individuals in the control group had longer durations of stay in MMT and fewer other kinds of treatment admissions during the study period. An 81 percent of individuals in the financially discharged group received other treatment episodes versus 0.3 percent in the control group (p < 0.001). More than twice the number of individuals financially discharged from MMT were incarcerated during the study period when compared with the control group (67 percent vs 33 percent, p < 0.001). In logistic regression analysis, individuals in the control group had 0.26 times the odds of incarceration when compared with individuals financially discharged from MMT (95% CI: 0.09-0.73). Conclusions: MMT has been shown to reduce involvement in the criminal justice system, yet cost of MMT continues to inhibit its accessibility. Our data suggest that removal of cost as a barrier to access MMT may facilitate longer treatment duration and minimize involvement with the criminal justice system.